Quaternary indoor organic photovoltaic device demonstrating panchromatic absorption and power conversion efficiency of 10%. (April 2019) - Shin, Sang-Chul; Vincent, Premkumar; Bae, Jin-Hyuk; Lee, Jae Joon; Nam, Minwoo; Ko, Doo-Hyun; Kim, Hyeok; Shim, Jae Won
Abstract: Recently, while increasing research has been focused toward improving the efficiency of various photovoltaic devices under low light intensities, few studies have reported on multi-donor-, multi-acceptor-based bulk heterojunctions (BHJ). In this study, we have demonstrated the utilization of a quaternary BHJ for indoor light energy harvesting applications. We utilized a PCDTBT:PTB7:PC61 BM:PC71 BM-based BHJ structure in order to improve the morphology, absorption window, and the charge transport properties of the photovoltaic device. The ability of ternary photovoltaics to attain high power-conversion efficiency (PCE) by improving the morphology and the charge transport properties had already been validated in another study. We show that the advantages of a stable quaternary solar cell can also be achieved with an optimized BHJ composition ratio of 5:5:3:12, which provides a PCE of 10.6%. Our device showed high shunt resistance and low series resistance, thus facilitating appreciable charge extraction even under low-intensity light conditions such as 500 lx white LED illumination. Graphical abstract: Highlights: Organic photovoltaics (OPVs) have shown to be promising for indoor energy harvesters. Complementary absorption of the incident spectrum can improve the short-circuit current density of the OPV. Requirement of careful optimization of active layer thickness was observed through optical simulation. Experiment verified that quaternary OPV can obtain 10% power-conversion efficiency under indoor LED illumination. 10% PCE was attained through complementary absorption and high shunt resistance of the OPV.